Journalistic Coverage of the Dollar Rise Crisis in the Iraqi Market from the Perspective of the Academic Elite: A Survey Study at the College of Arts, Wasit University - Alaa Azweer Dhumeed Al-Sarai, Asst. Lect. (lark, 2025)
In recent years, the Iraqi monetary market has experienced chaos due to the misjudgment of economic experts regarding the global financial crisis, which led to a loss of control over the exchange rate of the Iraqi dinar against the US dollar. Among the contributing factors to price fluctuations in the Iraqi market was the media’s role in disseminating false and misleading news and not fully conveying the truth, alongside other economic problems. Therefore, this study aims to highlight the journalistic coverage of the dollar rise crisis in the Iraqi market and propose media-based solutions to address this economic crisis. The study answers the main question: What is the academic elite’s perspective on the journalistic coverage of the dollar rise crisis in the Iraqi market? The research adopted a descriptive survey methodology, using a questionnaire distributed to the entire academic elite population, specifically faculty members of the Media Department at the College of Arts, Wasit University, using a comprehensive census method. The study included two main topics: the journalistic coverage and the crisis itself. Findings showed that media institutional dependency is one of the most influential factors affecting journalistic coverage of the dollar rise crisis. The majority of respondents indicated that journalistic reports are the most frequently used news genre in Iraqi newspapers for covering the crisis. Moreover, the primary attracting elements used by Iraqi newspapers in addressing the crisis were continuous presentation of comprehensive figures and statistics.
Keywords: : journalistic coverage, crisis, Iraqi market, academic elite.